2012
DOI: 10.1159/000337275
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among Salivary Carbonic Anhydrase VI Activity and Flow Rate, Biofilm pH and Caries in Primary Dentition

Abstract: This study aimed to determine the activity of carbonic anhydrase isoenzyme VI (CAVI) in the saliva of preschool children with caries and to investigate the relationship between caries and salivary CAVI activity, salivary flow rate and biofilm pH before and after a 20% sucrose rinse. Thirty preschool children aged 45.3–80.3 months were divided into two groups: a caries-free group and a caries group. Clinical examinations were conducted by one examiner (ĸ = 0.95) according to WHO criteria (dmfs) and early caries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 58 publications
3
45
1
6
Order By: Relevance
“…[19,[21][22][23] On the other hand, some of our results were not in agreement with other authors. [23][24][25] This conflict may be due to the difference in method of analysis as our study were able to determine the concentration of salivary CA VI while Frasseto et al [25] used the zymography method to quantitatively determine the activity of salivary CA VI. [24] Their results indicate significantly higher activity of CA in stimulated than non-stimulated saliva in both examined groups, while Surdilović et al [20] reported a positive correlation between CA VI concentration and saliva secretion.…”
Section: Resultsmentioning
confidence: 80%
“…[19,[21][22][23] On the other hand, some of our results were not in agreement with other authors. [23][24][25] This conflict may be due to the difference in method of analysis as our study were able to determine the concentration of salivary CA VI while Frasseto et al [25] used the zymography method to quantitatively determine the activity of salivary CA VI. [24] Their results indicate significantly higher activity of CA in stimulated than non-stimulated saliva in both examined groups, while Surdilović et al [20] reported a positive correlation between CA VI concentration and saliva secretion.…”
Section: Resultsmentioning
confidence: 80%
“…We based the sample power calculation (95%, α = 5%) on a study previously performed by our group [Frasseto et al, 2012] in which we used a similar methodology and found that the activity of CA VI in the saliva of caries and caries-free preschool children was 42.75 ± 32.47 and 19.13 ± 16.391, respectively. The sample size was based on the averages for two independent samples and a bilateral test (parametric test) with the equation: …”
Section: Samplementioning
confidence: 99%
“…In the same way, Szabó [1974] found a higher concentration of CA VI in saliva of 7-to 14-year-old caries-free children than in children with caries. However, the previous investigation by Frasseto et al [2012] employed the zymography method and quantitatively determined the activity of salivary CA VI. These authors demonstrated that after a cariogenic challenge the activity of salivary CA VI was higher in preschool children with dental caries.…”
mentioning
confidence: 99%
“…The importance of CA VI is evidenced by its involvement in several malfunctions. Low CA VI concentrations and activity in saliva were associated with the prevalence of dental caries [Kivelä et al, 1999;Frasseto et al, 2012]. Salivary bicarbonate secretion is also known to be important in the maintenance of esophageal pH homeostasis [Helm et al, 1984].…”
mentioning
confidence: 99%